(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The object of this study is the control of constitutionality and the effects, more precisely in a more onerous criminal law. Taking into account that the principle of proportionality is implicitly provided for in art. 5th, Inc. LIV, of the Federal Constitution, it is concluded that all legal norms in the Brazilian legal system must respect the aforementioned principle, under penalty of being considered unconstitutional. In this way, the control of constitutionality has the mission of allowing or not that a legal rule remains in force. From this angle, the objective of the present work is to analyze the possibility of carrying out the constitutionality control based on proportionality, regarding article 273 of the Penal Code for contradicting this principle.